Hubungan Kualitas Pelayanan Frontliner Dengan Kepuasan Pengunjung Di Bandar Udara Internasional Minangkabau - Meylani Irfana Sari; indria Flowerina (CV. ITTC INDONESIA, 2026)
The Purpose of This Research To find out whether there is a relationship between the quality of frontliner service and visitor satisfaction at Minangkabau International Airport. In this study, a descriptive statistical research type with a quantitative approach will be used that seeks to collect and measure data in the form of numbers in managing data that will be obtained from respondents. In this study, the population is visitors who received Frontliner service at Minangkabau International Airport in June 2024, totaling 523 visitors to Minangkabau International Airport. The sample size is calculated using the Slovin formula. Sampling in this study uses the Slovin formula and is randomized to all customers of Minangkabau International Airport. So that in this study, 84 visitors to Minangkabau International Airport were used as samples of this study. So that the overall results of the study show a significant relationship between Frontliner Service Quality and Customer Satisfaction at Minangkabau International Airport. This is indicated by the results of the T test that the calculated t value is 8,640> 1,984 t Where the calculated t value is greater than the t-table. The results of the coefficient of determination test indicate that the overall relationship between Service Quality and Customer Satisfaction is strongly correlated, with an average R-squared of 47.7%. The remaining 52.3% is influenced by other variables. Therefore, this study found that Frontliner Service Quality contributes significantly.